Tumour‐specific and organ‐specific protein synthesis rates in patients with pancreatic cancer. Issue 3 (13th March 2019) - van Dijk, David P.J.; Horstman, Astrid M.H.; Smeets, Joey S.J.; den Dulk, Marcel; Grabsch, Heike I.; Dejong, Cornelis H.C.; Rensen, Sander S.; Olde Damink, Steven W.M.; van Loon, Luc J.C.
Abstract: Background: Living tissues maintain a fine balance between protein synthesis and protein breakdown rates. Animal studies indicate that protein synthesis rates are higher in organs when compared with skeletal muscle tissue. As such, organ and tumour protein synthesis could have major effects on whole‐body protein metabolism in wasting disorders such as cancer cachexia. We aimed to assess protein synthesis rates in pancreatic tumour tissue and healthy pancreas, liver, and skeletal muscle tissue in vivo in humans. Methods: In eight patients with pancreatic cancer undergoing pancreaticoduodenectomy, primed continuous infusions with L‐[ring‐ 13 C6 ]phenylalanine and L‐[3, 5‐ 2 H2 ]tyrosine were started prior to surgery and continued throughout the surgical procedures. During surgery, plasma samples and biopsies from the pancreas, pancreatic tumour, liver, and vastus lateralis muscle were taken. Post‐absorptive fractional protein synthesis rates were determined by measuring incorporation of labelled L‐[ring‐ 13 C6 ]phenylalanine in tissue protein using the weighed plasma L‐[ring‐ 13 C6 ]phenylalanine enrichments as the precursor pool. Results: Five male patients and three female patients with a mean age of 67 ± 2 years were included into this study. Plasma L‐[ring‐ 13 C6 ]phenylalanine enrichments (6–9 mole per cent excess) did not change during surgery ( P = 0.60). Pancreatic tumour protein synthesis rates were 2.6‐fold lower than surrounding pancreatic tissue protein synthesis rates (0.268 ± 0.053 vs. 0.694 ± 0.228%/h, respectively; P = 0.028) and 1.7‐fold lower than liver protein synthesis rates (0.268 ± 0.053 vs. 0.448 ± 0.043%/h, respectively; P = 0.046). Among healthy organ samples, protein synthesis rates were 20‐fold and 13‐fold higher in pancreas and liver, respectively, compared with skeletal muscle tissue (0.694 ± 0.228 and 0.448 ± 0.043 vs. 0.035 ± 0.005%/h, respectively; P < 0.05). Conclusions: Liver and pancreas tissue protein synthesis rates are higher when compared with pancreatic tumour and skeletal muscle tissue protein synthesis rates and can, therefore, strongly impact whole‐body protein metabolism in vivo in humans.